تخطيط الضواحي السكنية وفق اتجاه العمران الجديد في مرحلة إعادة الإعمار في سورية. - مـي سلوم (Tishreen University, 2019)
ظهر اتجاه العمران الجديد كتيار عمراني في القرن العشرين في الولايات المتحدة الأمريكية، وجاء كرد على التوسع العمراني في أميركا بعد الحرب العالمية الثانية وازدياد استخدام وسائط النقل الحديثة حيث أصبح غالبية السكان يعيشون في الضواحي ويعملون في المدن. كما ظهر كاستجابة للمحاولات العديدة من قبل المعماريين والمخططين لتأمين السكن البيئي المستدام. من أهم أهداف الاتجاه الحد من استخدام السيارة والاعتماد على المشي والدراجات الهوائية، من خلال إيجاد مجاورات سكنية فيها كثافة عالية تحتوي على كل الخدمات اللازمة للمواطن من مدارس وعمل ومحلات تجارية وغيرها وعلى بعد مناسب للوصول إليها سيراً على الأقدام، يناقش البحث هذه المبادئ ويقوم بمحاولة تطبيق أفكارها على ضاحية قدسيا كنموذج محلي قائم، لمعرفة مدى إمكانية تطبيق التوجهات الحديثة وقراءة الدروس المستقاة واستنتاج بعض التوجهات العمرانية للاستعانة بها عند تخطيط الضواحي السكنية في سورية في مرحلة إعادة الإعمار. The new urbanism movement is an intellectual urban planning which has flourished during the twentieth century in America. The movement was an answer for the urban expansion in America after World War،П when the most residents wanted to live in the suburbs and to work in the cities. It was also an answer for many architects and urbanists' attempts to build the sustainable housing. The most important principles of the movement are to restrict the use of cars and enhance walking and biking by planning neighborhoods with high density which contain all the services needed and offices, stores and schools on an appropriate distance to be reached on foot. The research presents these principles and discusses to what extend they are related to an existing local model -Qodsaya suburb by firstly examining the success of the local model and secondly by measuring the extend we can relate the trend's principles to the local model. Finally the research concludes some points and recommendations to take into consideration in the planning of residential suburbs in Syria in the reconstruction phase.